CONTRIBUTION OF SUPERVISORS IN IMPROVING TEACHER COMPETENCE at MADRASAH ALIYAH PASAMAN - Israfina Israfina; Syaflin Halim; Rahmi Rahmi (Ruhama : Islamic Education Journal, 2021)
Madrasah supervisors have a responsibility in improving the competence of teachers in the institutions they supervise, therefore this research aims to know and analyze how supervisors perform their functions in improving teacher competence in MAN 1 Pasaman. This research is a descriptive research of non-statictic analysis using qualitative methods. Data is obtained through observation, interview and documentation studies. The data collected is then analyzed through three activities, namely data reduction, data presentation, and conclusion drawing. The results prove that: 1) Supervisors play an active role in providing advice and input to madrasah heads for activities to be carried out in order to improve teacher competence,  2) In the activities of improving teacher competence in MAN 1 Pasaman, supervisors act as mediators, facilitators, 3) Teacher competencies in MAN 1 Pasaman are evaluated by supervisors through a review of aspects that become the duties and responsibilities of teachers.